Comprehensive evaluation of microRNA as a biomarker for the diagnosis of hepatocellular carcinoma - Malik, Juliane; Klammer, Martin; Rolny, Vinzent; Chan, Henry Lik-Yuen; Piratvisuth, Teerha; Tanwandee, Tawesak; Thongsawat, Satawat; Sukeepaisarnjaroen, Wattana; Esteban, Juan Ignacio; Bes, Marta; Köhler, Bruno Christian; Lange, Magdalena Swiatek-de (World journal of gastroenterology, 2022)
Hepatocellular carcinoma (HCC) is the most common type of primary liver cancer. Current guidelines for HCC management recommend surveillance of high-risk patients every 6 mo using ultrasonography. Serum biomarkers, like alpha-fetoprotein (AFP), protein induced by vitamin K absence/antagonist-II (PIVKA-II) and lectin-reactive AFP, show suboptimal performance for detection of HCC, which is crucial for successful resection or treatment. Thus, there is a significant need for new biomarkers to aid early diagnosis of HCC. Studies have shown that the expression level of human microRNAs (miRNAs), a small, non-coding RNA species released into the blood, can serve as an early marker for various diseases, including HCC.